2002
DOI: 10.3346/jkms.2002.17.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Old Abdominal Pregnancy Presenting as an Ovarian Neoplasm

Abstract: INTRODUCTIONThe incidence of abdominal pregnancy varies from one in 372 to one in 9,714 live births; and the abdominal pregnancy is associated with high morbidity and mortality (1). The lithopedion formation, a dead fetus undergoing intra-abdominal calcification instead of spontaneous resorption, is an unusual complication. There has been only a single report on presentation of lithopedion as an ovarian neoplasm in the literature (2). We herein report the second such case. CASE REPORTA 63-yr-old, gravida 2, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 5 publications
0
17
0
5
Order By: Relevance
“…Algunos autores consideran que la intervención por intermedio de cirugía en esos casos es necesaria, pero otros no observaron efectos indeseables en pacientes que no se sometieron a ese procedimiento (15). La morbilidad aumenta cuando se realiza la operación en una paciente anciana (16). De acuerdo a esas informaciones, los médicos concordaron que la cirugía no era necesaria, una vez que se trataba de una paciente anciana y sin complicaciones, a pesar de los episodios recurrentes de dolor abdominal durante años.…”
Section: Discussionunclassified
“…Algunos autores consideran que la intervención por intermedio de cirugía en esos casos es necesaria, pero otros no observaron efectos indeseables en pacientes que no se sometieron a ese procedimiento (15). La morbilidad aumenta cuando se realiza la operación en una paciente anciana (16). De acuerdo a esas informaciones, los médicos concordaron que la cirugía no era necesaria, una vez que se trataba de una paciente anciana y sin complicaciones, a pesar de los episodios recurrentes de dolor abdominal durante años.…”
Section: Discussionunclassified
“…Differential diagnosis includes ovarian tumours [6], myomas, teratoma, inflammatory masses and urinary tract or bladder tumours [3]. Surgical removal is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Passini et al [20] found fewer than 300 reported cases in 400 years of world medical literature; however, from 1968 to 1999 at least 47 new cases of lithopaidion were published. Moreover, it has been confirmed that in the last 10 years, as prenatal care and surveillance have increased, the presentation of lithopaidions is rare [28], even though at least 17 cases of lithopaidions were demonstrated in the last century [1,20,23,25,28,29,30,31,32,33,34,35,36,37,38,39,64]; only in this case, we have not considered the 4 cases of lithopaidions reported by Sunday-Adeoye et al [40] because it was not possible to determine the exact century of their occurrence. However, a complete analysis of the English literature has revealed more than 330 case of lithopaidion so far.…”
Section: Epidemiologymentioning
confidence: 99%
“…Frequent symptoms are abdominal/pelvic pain (even if its character is variable), abdominal/pelvic heaviness (that is not specific) and compression syndromes particularly affecting the urinary tract and bowel (table 5). The differential diagnosis on the presentation of lithopaidion may include ovarian neoplasm [32], myomas, inflammatory masses, epiploon calcifications, and urinary tract or bladder tumors [45]. …”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation